2013
DOI: 10.3892/br.2013.123
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of XPD and hOGG1 genetic variants to prostate cancer

Abstract: Abstract. DNA repair genes are important in maintaining genomic stability and integrity. DNA repair gene polymorphisms, such as those of the human homolog of 8-oxoguanine DNA glycosylase 1 (hOGG1) and excision repair cross-complementing rodent repair deficiency, complementation group 2̸Xeroderma pigmentosum complementation group D (ERCC2̸XPD), contribute to carcinogenesis. The aim of this study was to investigate the association of prostate cancer (PCa) risk with hOGG1 and ERCC2̸XPD genetic variants. A case-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…There is a possibility of a type II error in this part of the analysis probably due to insufficient power. hOGG1 Ser326cys polymorphism has been shown to be significantly associated with other cancers, namely nasopharynx [20], esophageal [43], lung [44] and prostate cancer [45]. The ability of wildtype hOGG1 Ser326 to suppress mutagenesis was found to be stronger than the variant hOGG1 Cys326 [15].…”
Section: Discussionmentioning
confidence: 94%
“…There is a possibility of a type II error in this part of the analysis probably due to insufficient power. hOGG1 Ser326cys polymorphism has been shown to be significantly associated with other cancers, namely nasopharynx [20], esophageal [43], lung [44] and prostate cancer [45]. The ability of wildtype hOGG1 Ser326 to suppress mutagenesis was found to be stronger than the variant hOGG1 Cys326 [15].…”
Section: Discussionmentioning
confidence: 94%
“… 16 Mutations in DNA repaired gene may lead to decrease or loss of its DNA repair capacity and confer the variation in susceptibility to diverse malignant tumors among individuals. Many studies have indicated that polymorphisms in DNA repair genes may modify the risk for cancer, such as esophageal cancer, breast cancer, glioma and prostate cancer, 17 - 20 while few studies reported the role of DNA repair genes and development of osteosarcoma. 21 …”
Section: Discussionmentioning
confidence: 99%
“…Mirecka et al 12 showed that the Arg156Arg polymorphism has no relationship with PCa risk. However, the results reported by Zhou et al 13 indicated that Arg156Arg polymorphism increased the susceptibility to high-risk PCa. No meta-analysis has yet been conducted to explore the relationship between the Arg156Arg polymorphism in XPD and the risk of PCa.…”
Section: Introductionmentioning
confidence: 90%